A Novel Sulfonyl-Based Small Molecule Exhibiting Anti-cancer Properties - El-Kadiry, Abed El-Hakim; Abusarah, Jamilah; Cui, Yun Emma; El-Hachem, Nehme; Hammond-Martel, Ian; Wurtele, Hugo; Thomas, Sini; Ahmadi, Maryam; Balood, Mohammad; Talbot, Sébastien; Rafei, Moutih (Frontiers in Pharmacology, 2020)
Phenotypic screening is an ideal strategy for the discovery of novel bioactive molecules. Using a customized high-throughput screening (HTS) assay employing primary T lymphocytes, we screened a small library of 4 398 compounds with unknown biological function/target to identify compounds eliciting immunomodulatory properties and discovered a sulfonyl-containing hit, we named InhiTinib. This compound inhibited interferon (IFN)-gamma production and proliferation of primary CD3+ T cells without inducing cell death. In contrast, InhiTinib triggered apoptosis in several murine and human cancer cell lines. Besides, the compound was well tolerated by immunocompetent mice, triggered tumor regression in animals with pre-established EL4 T-cell lymphomas, and prolonged the overall survival of mice harboring advanced tumors. Altogether, our data demonstrate the anti-cancer properties of InhiTinib, which can henceforth bridge to wider-scale biochemical and clinical tests following further in-depth pharmacodynamic studies.